TECHNIQUE FOR ORDER PREFERENCE METHOD BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) FOR DECISION SUPPORT SYSTEM IN DETERMINING THE PRIORITY FOR RECEIVING VILLAGE FUND ASSISTANCE - Mutiara Andayani; Nur Yanti; Lusiyanti Lusiyanti (Jurnal Mantik, 2022)
In the modern era filled with global competition, now competition in realizing good and equitable infrastructure development has become the main focus in almost all specialty areas in Sub-districts throughout Indonesia. In STM Hulu Tiga Juhar Subdistrict, Deli Serdang Regency, they are now actively developing infrastructure, but are still constrained by several problems. One of the problems in determining the priority of receiving Village Fund assistance is still not accurate and still uses the manual method so it can lead to errors in determining the priority of receiving Village Fund assistance. To avoid things that are not desirable in determining priorities for receiving Village Fund assistance, it turns out that there are several techniques that can be used in determining priorities for receiving Village Fund assistance with a Decision Support System (SPK). By using the Decision Support System application in determining the Priority for Receiving Village Fund Assistance using the TOPSIS method at the STM Hulu Tiga Juhar sub-district office, the problems faced by the STM Hulu Tiga Juhar sub-district office can be resolved so that in determining the Priority for receiving Village Fund Aid is faster, more accurate. and accurate to avoid errors.